2016
DOI: 10.1093/arclin/acv089
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Variables That May Affect the Relationship Between Cognition and Functional Status in Individuals with Mild Cognitive Impairment: A Meta-Analysis

Abstract: The objective of this meta-analysis was to improve understanding of the heterogeneity in the relationship between cognition and functional status in individuals with mild cognitive impairment (MCI). Demographic, clinical, and methodological moderators were examined. Cognition explained an average of 23% of the variance in functional outcomes. Executive function measures explained the largest amount of variance (37%), whereas global cognitive status and processing speed measures explained the least (20%). Short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
75
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 64 publications
8
75
2
1
Order By: Relevance
“…More specifically, poorer performances on tests of executive functioning (switching) and temporal order memory were related to poorer self-reported everyday functioning for the high SCC group. This pattern of findings is consistent with the literature, which suggests that memory and executive functioning, are related to everyday functioning in the older adult population and MCI populations (e.g., Farias et al, 2009; Jefferson, Paul, Ozonoff, & Cohen, 2006; McAlister, Schmitter-Edgecombe, & Lamb, 2016; Schmitter-Edgecombe & Parsey, 2014b). Further examination of the cognitive domains that may predict functional performance in individuals with SCC and their neural underpinnings may serve to refine the neuropsychological profile of SCC and development of sensitive cognitive tests.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…More specifically, poorer performances on tests of executive functioning (switching) and temporal order memory were related to poorer self-reported everyday functioning for the high SCC group. This pattern of findings is consistent with the literature, which suggests that memory and executive functioning, are related to everyday functioning in the older adult population and MCI populations (e.g., Farias et al, 2009; Jefferson, Paul, Ozonoff, & Cohen, 2006; McAlister, Schmitter-Edgecombe, & Lamb, 2016; Schmitter-Edgecombe & Parsey, 2014b). Further examination of the cognitive domains that may predict functional performance in individuals with SCC and their neural underpinnings may serve to refine the neuropsychological profile of SCC and development of sensitive cognitive tests.…”
Section: Discussionsupporting
confidence: 91%
“…Although it remains unclear as to which cognitive abilities are most predictive of everyday functioning, memory and executive functioning appear to be the most widely investigated and frequent predictors of functional status in both HOAs and older adults with MCI (e.g., Cahn-Weiner, Boyle, & Malloy, 2002; McAlister, Schmitter-Edgecombe, & Lamb, 2016; Schmitter-Edgecombe, McAlister, & Weakley, 2012; Vaughan & Giovanello, 2010). Recent studies have also indicated that noncontent memory processes (i.e., prospective memory and temporal order memory), which have been linked to executive functioning and the frontal lobes (e.g., Glisky & Kong, 2008; Turner, Simons, Gilbert, Frith, & Burgess, 2008), make an independent contribution to the prediction of functional abilities in both HOAs and MCI (e.g., McAlister & Schmitter-Edgecombe, 2013; Schmitter-Edgecombe et al, 2012; Schmitter-Edgecombe, Woo, & Greeley, 2009; Woods, Weinborn, Velnoweth, Rooney, & Bucks, 2012).…”
mentioning
confidence: 99%
“…These findings are consistent with prior research showing that switching abilities are important for functional abilities in HOAs (e.g., Bell-McGinty et al, 2002) and individuals with cognitive impairment (e.g., McAlister, Schmitter-Edgecombe, & Lamb, 2016; Yeh et al, 2011). Moreover, in contrast with several other studies of HOAs (i.e., Jefferson et al, 2006; Han, 2010), the results from the regression analyses did not show inhibition abilities to be strong predictors of everyday functioning despite both of our inhibition tasks likely measuring different aspects of inhibition (behavioral versus oculomotor).…”
Section: Discussionsupporting
confidence: 92%
“…For example, a recent meta-analyses found that across multiple cognitive domains and neuropsychological measures, TMT-B accounted for the largest amount of variance in functional status in mild cognitive impairment (McAlister, Schmitter-Edgecombe, & Lamb, 2016). TMT-B has also been found to be a predictor of medication management ability in Parkinson’s disease (Manning et al, 2012), and instrumental activities of daily living in community-dwelling older adults (Bell-McGinty, Podell, Franzen, Baird, & Williams, 2002; Cahn-Weiner, Boyle, & Malloy, 2002).…”
Section: Introductionmentioning
confidence: 99%